Tafsir al-Fiqh in Andalus: A Historical-Comparative Studies of Ahkām al-Qur’ān by Ibn al-’Arabi and Al-Jāmi‘ li Ahkām al-Qur’ān by al-Qurtubi - Moh Sabiq BA; Imron Izzul Haq (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This article examines two books of tafsir entitled Ahkam al-Qur'an by Ibn al-'Arabi and Al-Jami' li Ahkam al-Qur'an by al-Qurtubi as a comparison study. Both were written by Andalusian scholars (mufassir). The main issue that is answered is how the method used by Ibn al-'Arabi and al-Qurtubi in interpreting legal verses. What are the similarities and differences in their interpretations in the context of Islam in Andalusia at that time? There are two factors for this research. First, these tafsir fully interpret the legal verses (30 Juz) and adhere to Maliki’s jurisprudence. Second, both of these tafsir were written at different times and places. Therefore, the author attempts to find common ground for similarities and differences between the interpretations of Ibn al-‘Arabi and al-Qurtubi through a historical approach. Furthermore, the author uses Norman Fairclough’s theory of Critical Discourse Analysis in this research. This article has several conclusions and arguments. First, Ibn al-'Arabi and al-Qurtubi use the tahlili (analytical) method, interpreting verses in detail into several points of issue and loaded with the aqwal al-ma'tsur. Regarding verse selection, Ibn al-'Arabi only focuses on interpreting certain legal verses in each surah. Al-Qurtubi interpreted all verses in the Qur'an. Second, based on the analysis of his biographical history and educational career, Ibn al-'Arabi's interpretation tends to be conservative due to the fanaticism of the mazhab and the intervention of the Murabitun dynasty. Al-Qurtubi's interpretation tends to be neutral and more ethical due to the many rebellions and rejection of the Maliki school and the emergence of Sufism under the rule of the Muwahidun dynasty until its collapse.